Language Competence and Language Performance of Preschool Children - Milinchuk, Volodymyr (Psychological Prospects Journal, 2016)
The article is focused on the aspects of language ability and language performance in the context of children’s speech development. Language ability is defined as level of acquisition of lexical and grammatical aspects of language. Language ability is often identified with language competence. Perception of linguistic representation is based on linguistic signal, or stimulus. This process is psycholinguistic activity, since it can not take place without language competence. Language knowledge is important for an individual to reproduce and perceive phonological representation of linguistic signal. There exist a clear succession in the language development and acquisition that does not depend on a certain language being acquired, although some of its aspects can seem less difficult to learn than others. This succession in the language development and acquisition is determined by psychophysiological, neuropsychological and social-cultural factors of speech activity. The results of the empirical study prove the fact that the levels of language ability and language performance are not enough for efficient speech activity. Future directions of the study foresee the psychological and pedagogical support for speech development of the children of preschool age.Keywords: language competence, language performance, children’s speech, conceptual thinking, speech activity.